Soluble immune checkpoint landscape in sickle cell disease links systemic inflammation, autoimmunity, and pain - Li, Wei; Pucka, Andrew Q.; Houran, Lina; Huang, Xiaoqing; Debats, Candice; Reyes, Brandon A.; O’Brien, Andrew R. W.; Yu, Qigui; Wang, Ying (Frontiers in Hematology, 2025)
BackgroundSickle cell disease (SCD) is a chronic condition characterized by inflammation, immune dysregulation, and debilitating pain.AimThis study investigates soluble immune checkpoints (sICPs) and their associations with inflammatory mediators, immune cell profiles, autoantibodies, and clinical outcomes in SCD.MethodPeripheral blood samples from 50 SCD patients and 40 demographic-matched healthy controls (HCs) were analyzed for 37 sICPs, 80 inflammatory mediators, and 18 autoantibodies using multiplex assays, alongside immune cell profiles via flow cytometry. Pain and quality of life (QoL) were assessed through patient-reported outcome measures (PROMs).ResultsTwenty-three sICPs, including arginase-1, BTLA, CD27, CD28, CD47, CD80, CD96, CD134, CD137, CD152, GITR, HVEM, IDO, LAG-3, MICA, MICB, Nectin-2, PD-1, Siglec-7, Siglec-9, TIM-3, TIMD-4, and VISTA, were significantly elevated in SCD patients compared to HCs. These sICPs correlated with multiple proinflammatory mediators (e.g., IL-18), autoantibodies (e.g., MPO), and immune cell activation markers (e.g., CD38/HLA-DR on CD8 T cells). Notably, CD28, CD152, HVEM, and VISTA were strongly associated with systemic inflammation and immune cell activation, while BTLA, LAG-3, PD-1, and CD80 correlated with pain and anxiety scores and QoL.ConclusionThis study highlights complex interactions between sICPs, immune activation, inflammation, and clinical outcomes in SCD, underscoring their potential as biomarkers or therapeutic targets to alleviate inflammation and improve QoL in this challenging clinical population.